Two new species of Entomobrya Rondani (Collembola, Entomobryidae) from northeastern Brazil and comments on the genus - Da Cunha Santos, Nathália Michelly; Dos Santos-Costa, Renata Clicia; Siqueira, Orquianne Judy Rafael; Godeiro, Nerivânia Nunes; Bellini, Bruno Cavalcante (Zootaxa, 2020)
Entomobrya Rondani, 1861 is one of the largest genera of springtails and the most diverse group of scaleless Entomobryoidea. Only 14 species of Entomobrya were recorded from Brazil so far. Herein we present two new Brazilian species of the genus. Entomobrya juneae sp. nov. can be diagnosed by antennae shorter or as long as the trunk; prelabral and labial chaeta e smooth, mesothorax lacking m5 and p5 macrochaetae, mucro distal tooth reduced, among other features. It is somehow similar to E. atrocincta Schött, 1896 and E. nivalis (Linnaeus, 1758) sensu Katz et al. (2015) in some aspects of dorsal chaetotaxy, but the new species presents less macrochaetae on mesothorax and third and fourth abdominal segments. Entomobrya barbata sp. nov. is quite similar to E. linda Soto-Adames 2002 especially due to its remarkable reduced dorsal chaetotaxy, but can be separated from it in dorsal head, mesothorax, fourth abdominal segment and manubrial plate chaetotaxy. We also investigate the similarities of Brazilian Entomobrya species with Entomobryoides Maynard, 1951 and provide comments on the morphology of both genera.